The Influence of Hierarchy Steepness on Cooperation: A Comparison Between Captive Japanese Macaques and Black-handed Spider Monkeys - (:unkn) unknown (My University, 2017)
Non-human primates often live in social groups that form hierarchies, which can be either egalitarian or despotic. Despotic non-human primate groups are characterized by the ability of dominant members to frequently win dyadic conflicts against subordinates, and egalitarian primate groups are characterized by an unclear ranking of dominance. Non-human primates will often cooperate with each other within their social groups. Cooperation can be defined as the sharing of food, grooming, and formation of alliances. In a comparative study between bonobos (Pan paniscus) and chimpanzees (Pan troglodytes), it was suggested that hierarchy steepness is a good predictor of sharing between unrelated individuals, and sharing was directed more unilaterally from subordinate to dominant among the more despotic bonobos (Jaeggi, Stevens, & Schaik, 2010). In contrast, another study found that the introduction of shareable resources and induced cooperation can also reinforce rank between members and members will aggregate into groups of similar rank (Pansini, 2011). The goal of this research is to further elucidate the role that hierarchies play in forming reciprocal relationships between members by comparing two captive populations. The hypothesis of this thesis is that if the hierarchy of a primate group is despotic then there will be less cooperation between individuals, and if a primate group is egalitarian then there will be more cooperation between members. A group of despotic Japanese macaques (Macaca fuscata) was compared to the more egalitarian black-handed spider monkeys (Ateles geoffroyi). This study observed the grooming patterns, spatial associations, agnostic behaviors, and transfer of food between individuals and tested to see if there was evidence of reciprocity. The investigation also tested to see if exchanges of grooming and food were directed unilaterally from subordinate to dominant in both groups. It was expected that more despotic Japanese macaques would exchange food and grooming unilaterally towards rank, and that the more egalitarian black-handed spider monkey would provide food and grooming if they received food and grooming. It was found that there was no evidence for reciprocity or unilateral exchange of food and grooming in either primate group. Instead, it could be argued that while hierarchical steepness within a group can influence the flow of food and grooming, the environment also influences the exchanges of food and grooming between members. In environments in which members do not need to compete, there may be an absence of directionality in the exchange food and grooming.
Keywords: Cooperation; Hierarchy; Japanese Macaque; Spider Monkey